KERUSAKAN TERUMBU KARANG AKIBAT PROSES BIOLOGIS - Hanny Tioho & Kakaskasen (PPLH-SDA, Lembaga Penelitian Unsrat Manado, 2012)
The major agents of biological destruction of coral reefs can be divided into grazers, etchers and borers. Each of these groups is reviewed on a world wide basis, together with the mechanisms by which they destroy the coral substrate. Rate of bioerosion attributed to major agents of grazers, etchers and borers are given, together with limitations of some of the measurements. Factors which may be responsible for this variability are discussed. Although the review concentrates mainly on present day reefs, some attempt is made to consider the impact of bioerosion on older reefs.